Investigating the 8.2 ka event in northwestern Madagascar: Insight from data–model comparisons. (15th January 2019) - Voarintsoa, Ny Riavo G.; Matero, Ilkka S.O.; Railsback, L. Bruce; Gregoire, Lauren J.; Tindall, Julia; Sime, Louise; Cheng, Hai; Edwards, R. Lawrence; Brook, George A.; Kathayat, Gayatri; Li, Xianglei; Michel Rakotondrazafy, Amos Fety; et al.
Abstract: The 8.2 ka event is a well-known cooling event in the Northern Hemisphere, but is poorly understood in Madagascar. Here, we compare paleoclimate data and outputs from paleoclimate simulations to better understand it. Records from Madagascar suggest two distinct sub-events (8.3 ka and 8.2 ka), that seem to correlate with records from northern high latitude. This could indicate causal relationships via changes in the Atlantic Meridional Overturning Circulation (AMOC) with changes in moisture source's δ 18 O, and changes in the mean position of the Inter-Tropical Convergence Zone (ITCZ), as climate modelling suggests. These two sub-events are also apparent in other terrestrial records, but the climatic signals are different. The prominent 8.2 ka sub-event records a clear antiphase relationship between the northern and southern hemisphere monsoons, whereas such relationship is less evident during the first 8.3 ka sub-event. Data–model comparison have also shown a mismatch between the paleoclimate data and the model outputs, the causes of which are more or less understood and may lie in the proxies, in the model, or in both data and model. Knowing that paleoclimate proxies and climate models produce different sets of variables, further research is needed to improve the data–model comparison approach, so that both paleoclimate data and paleoclimate models will better predict the likely climate status of a region during a specified time in the past with minimal uncertainties. Highlights: The '8.2 ka event' is marked by two wet pulses (8.3 and 8.2 ka) in Northwestern Madagascar. Model suggests southward migration of ITCZ during the 8.2 ka event via changes in AMOC. Climate in Madagascar is tele-connected with climate in other monsoonal regions. Changes in Madagascar stalagmite δ 18 O may reflect changes in moisture source's δ 18 O. A mismatch between proxies and simulation outputs exists, and requires more research.